2010
DOI: 10.1186/1476-511x-9-63
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in lipid desaturases and its impact on the development of human disease

Abstract: Perturbations in lipid metabolism characterize many of the chronic diseases currently plaguing our society, such as obesity, diabetes, and cardiovascular disease. Thus interventions that target plasma lipid levels remain a primary goal to manage these diseases. The determinants of plasma lipid levels are multi-factorial, consisting of both genetic and lifestyle components. Recent evidence indicates that fatty acid desaturases have an important role in defining plasma and tissue lipid profiles. This review will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 69 publications
4
106
2
Order By: Relevance
“…More specifically, 583 genes were upregulated and 708 were downregulated in the WMs, whereas 628 genes were upregulated and 670 were downregulated in the WRs. The most significant downregulated gene in both WM and WR was stearoyl-CoA desaturase (SCD1; WMs: 23.4-fold; WRs: 22.5-fold), the ratelimiting enzyme responsible for the conversion of SFAs into MUFAs (30). Expression changes for SCD1 were confirmed by real-time RT-PCR (WMs: 21.8-fold; WRs: 22.0-fold; P , 0.05).…”
Section: Effects Of Lcd-induced Weight Loss On Gene Expression In Wmsmentioning
confidence: 64%
“…More specifically, 583 genes were upregulated and 708 were downregulated in the WMs, whereas 628 genes were upregulated and 670 were downregulated in the WRs. The most significant downregulated gene in both WM and WR was stearoyl-CoA desaturase (SCD1; WMs: 23.4-fold; WRs: 22.5-fold), the ratelimiting enzyme responsible for the conversion of SFAs into MUFAs (30). Expression changes for SCD1 were confirmed by real-time RT-PCR (WMs: 21.8-fold; WRs: 22.0-fold; P , 0.05).…”
Section: Effects Of Lcd-induced Weight Loss On Gene Expression In Wmsmentioning
confidence: 64%
“…This introduces a nutrigenomics approach to disease control and prevention 7 . Polymorphisms in the genes encoding Δ5-and Δ6-desaturases, FADS1 and FADS2 respectively (chromosome 11q12-11q13.1), have been associated with PUFA and LC PUFA status and cholesterol levels.…”
Section: Fatty Acid Pathophysiology and Gene Interactionsmentioning
confidence: 99%
“…The beneficial effects of breast feeding can be altered by the mother-infant-pair genotype. Gene-diet interactions should be taken into account when investigating the effects of maternal diet on the offspring health 7 .…”
Section: Fatty Acids As Biocompounds: Their Role In Human Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have observed that SNPs and microindels have been implicated in drug metabolism via their encoding gene-CYP2D6 with loss of enzyme activity and slow metabolism [50,51]. Alterations in the FADS enzyme genes are associated with the variations in the activity of these enzymes [52,53] as well as the K-ras gene in some other patient groups. Polymorphism in the genes coding for the FADS enzymes have been discovered in genome wide association studies by Guan et al [54].…”
Section: Background Inflammation In Sickle Cellmentioning
confidence: 99%